Challenges Towards Reducing Illegal Dumping Activities in the Construction Industry - Abd Rahim, Mohd Hilmi Izwan; Mohamed, Sulzakimin; Kasim, Narimah; Rahmat, Mazianah; Azmi, Nurdiana (Journal of Social Transformation and Regional Development, 2021)
Nowadays an increasing number of construction projects in Malaysia have contributed to the production of construction waste which has had a negative impact on the environment, especially through illegal dumping. The increasing number of illegal dumping activities is a sign that construction waste management needs to be examined. To date, a comprehensive criterion for construction waste management, in developing countries is still not clearly defined. Therefore, the objectives of this paper are to investigate current illegal dumping activities, and identify the challenges towards reducing illegal dumping activities in the Malaysian construction industry. Hence, this research conducted interviews with 20 expert stakeholders related to construction waste management in order to scrutinise illegal dumping activities in Malaysia. The data from these semi-structured interviews were analysed by content analysis. The findings are used to determine the current challenges for reducing illegal dumping activities in the Malaysian construction industry. The elements in the current findings are potentially to improve construction waste management in order to archive the proper construction waste management. Finally, this findings will help to identify strategies to reduce illegal dumping activities and to enhance challenges towards reducing illegal dumping activities in the Malaysian construction industry.